DIFFERENCES IN SPORT INTERESTS IN FEMALE ADOLESCENTS WITH VARIOUS OCCUPATIONAL CHOICES - Prot, Franjo; Bosnar, Ksenija; Gošnik, Jelka Vukmir, Vedrana (2005)
On the sample of 327 nature science high school female students, aged 17 to 20 years, attending five different high school vocational programs (cosmeticians, ecology technicians, geology technicians, chemical laboratory assistants and chemical industrial technicians) sport preference questionnaire was applied. Questionnaire consists of list of 25 sports chosen to be representatives of five sport interest factors: (1) factor of traditional sports, defined by swimming, skiing, sports gymnastics, athletics, and cycling ; (2) team sports factor, including volleyball, basketball, football, handball, and field hockey ; (3) combat sports factor, including judo, box, taekwondo, wrestling and karate ; (4) factor of sports with marked aesthetic component, including skating, rhythmic gymnastics, dance, diving and synchronised swimming, and (5) factor of outdoor and adventurous sports, defined by scuba diving, mountaineering, watter skiing, surfing and parachuting. The difference in sport interests in groups defined by five vocational programs was established by canonical discriminant analysis of orthogonalised factor scores from confirmatory factor analysis. Two statistically significant discriminant functions were found identified as general rejectance and acceptance of sport, and team sports oposed to traditional and outdoor sports dimension. First dimension differ ecology technicians attending elite educational program at the accepting sports side of the discriminant function from the other groups. Second dimension differs, in Holland's terms, investigative chemical laboratory assistants on traditional and outdoor sports side, and realistic geology technicians at the team sports side of discriminant function.
Projekt MZOS
ENG